The Dark Side of the Lasem Maritime Industry: Chinese Power in Opium Business in the XIX Century - Siska Nurazizah Lestari; Nara Setya Wiratama (Diponegoro University, 2018)
Some of the issues discussed in this article are the shipyard industry development at Lasem, and revealing the factors of Chinese traders conducted smuggling by sea. This study shows the dark side of the maritime industry found in Lasem mainly related to Chinese power in the opium business, XIX century. These problems analyzes with critical historical methods which consist of four stages, including a) heuristics, seeking and collecting historical sources, both primary and secondary sources; b) source criticism, the process carried out to test the authenticity and credibility of the source; c) interpretations, interpret and compile facts from one another; d) historiography, the process of rewriting historical events. According to the results, there was a concentration of Chinese residences during the colonial period. Lasem’s Chinese settlements (Chinatown) had rapid growth after the migration of Chinese and the Chinese massacre as known as Geger, Pecinan. To maintain its existence, the Chinese in Lasem initiated the opium business, developed in the nineteenth century by sea. The presence of the Lasem River also strengthened this finding, became the lifeblood of economic activity in the past. The Lasem River also connects the hinterland with the coastal area, so it has a negative impact mainly related to the smuggling of opium.